Mycosynthesis of chitosan-selenium nanocomposite and its activity as an insecticide against the cotton leafworm Spodoptera littoralis - Sohila A. Ibrahiem; Fifi M. Reda; Eman M. Abd-ElAzeem; Mostafa S. Hashem; Hala A. Ammar (Scientific Reports)
Abstract The cotton leafworm, Spodoptra littoralis, causes great damage to cotton crops. A new, safer method than insecticide is necessary for its control. Selenium nanoparticles (SeNPs) are metalloid nanomaterial, with extensive biological activities. They have low toxicity and can be used safely in plant disease management. In this study, we successfully bio-fabricated selenium nanoparticles and chitosan-selenium nanocomposite (Ch-SeNPs) using a fungal cell-free filtrate of Penicillium griseofulvum. The biosynthesized nanomaterials were initially detected optically by the formation of a red color in the solution mixture and the appearance of a strong plasmon resonance peak at 240–300 nm. The biosynthesized nanomaterials were fully characterized by UV–visible spectroscopy, transmission electron microscopy, dynamic light scattering, energy dispersive X-ray, inductively coupled plasma spectroscopy, and Fourier transform infrared. We tested the anti-insect activities of SeNPs, and Ch-SeNPs against larvae of S. littoralis compared to spore suspensions of P. griseofulvum. The results indicated that Ch-SeNPs followed by SeNPs gave a significantly higher mortality percentage than the spore suspension of the tested fungus. The highest production of all biosynthesized nanomaterials was detected after 7 days at 40 °C under alkaline conditions (pH 9). The average size diameter of SeNPs and Ch-SeNPs were 91.25 and 67.41 nm with zeta potential − 8.05 and + 41 mV, respectively. Both Ch-SeNPs and SeNPs gave high mortality rates and low values of LC50 and LC90 for both larvae and pupae. Ch-SeNPs showed stronger activity against S. littoralis than SeNPs and spore suspension at all experimental conditions. Cytotoxicity experiments indicated their safety against honeybee populations. The current study reveals the significant ultrastructure impact of SeNPs on larvae. These findings suggest that selenium nanoparticles and nanocomposite can be fabricated with a costless easy route using fungal filtrate, and they can be used safely in pest control systems that are safe for honeybee populations. It is the first report about the application of Ch-SeNPs as an anti-insect agent.